Internationalization processes of Finnish software firms : the influence of network relationships and product and the synergy between them - Mannonen, Anne (2020)
Internationalization processes of small- and medium-sized software enterprises have been studied largely in terms of network relationships. The interaction between networks and product, though, has been investigated less in the literature. The emphasis in this master’s Thesis is the importance of network and product plus their synergy in the internationalization process of software firms. Other affecting factors raised in the interviews have also been included into this paper. The study contains the literature review and the empirical part. Research and studies regarding network relationships and product are introduced in the literature review. The empirical part was conducted as a qualitative case study, thus, employees of five firms were interviewed. The interviews revealed that firms have similarities and differences in their internationalization processes. In general, the findings support previous research: both networks and product/service/innovation are essential in the internationalization process. Neither networks nor product was considered superior according to the representatives of the firms although the quality of the product is crucial in the beginning of the internationalization process. Success in the global market is mainly due to several factors, not only depending on creating networks and product or its R&D.